Culto y Peregrinaje Inka en el Nevado de Cachi, Salta, Argentina. Nuevos datos en Arqueología de Alta Montaña. (3rd July 2018) - Leibowicz, Iván; Moyano, Ricardo; Ferrari, Alejandro; Acuto, Félix; Jacob, Cristian
Abstract : This work presents new results of archaeological research carried out in a mountain massif known as Nevado de Cachi (Salta, Argentina). We will focus on an Inka ceremonial platform located near the summit of Cerro Meléndez (6020 masl), which is one of its most prominent peaks, and integrate this information with data collected on two archaeological settlements located on its hillsides to the east. We will argue that a complex system of archaeological settlements and sacred places which included local and Inka enclosures, was designed not only for mountain worship but also as the manifestation of the Inka conquest of the North Calchaquí Valley. Thus, the existence of a complex system of settlements and sacred Inka sites in the Nevado de Cachi is highlighted.